Analisis Mekanisme Pembagian Komisi Penjualan Barang Konsinyasi Pada Pelaku Usaha Makanan Ringan Desa Sidodadi, Sekampung, Lampung Timur - Carmidah Carmidah; Asnanil Khoiriyyah; Carissa Laura Eka Putri; Ma’rifatul Fuadah; Yusuf Abdurrahman (Jurnal Akuntan Publik, 2024)
This research was conducted to analyze the mechanism for distributing commissions for sales of consignment goods to snack business actors in Sidodadi Village, Sekampung, East Lampung. Research was conducted on two cassava cracker making home industries, namely the Pelangi Cassava Cracker Home Industry and the Satria Cassava Cracker Home Industry which implemented a consignment sales system. Data was obtained through interviews with business owners. The research results show that there are differences in basic prices and commissions between the two home industries which are influenced by several factors. The recording system for consignment sales has not been fully implemented. It was concluded that the commission distribution mechanism had been carried out based on an agreement, but consignment accounting records had not been implemented completely.